2012
DOI: 10.1302/0301-620x.94b6.28680
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcome of massive intercalary bone allografts in the treatment of tumours of the femur

Abstract: We retrospectively reviewed 101 consecutive patients with 114 femoral tumours treated by massive bone allograft at our institution between 1986 and 2005. There were 49 females and 52 males with a mean age of 20 years (4 to 74). At a median follow-up of 9.3 years (2 to 19.8), 36 reconstructions (31.5%) had failed. The allograft itself failed in 27 reconstructions (24%). Mechanical complications such as delayed union, fracture and failure of fixation were studied. The most adverse factor on the outcome was the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
4
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 34 publications
7
71
4
3
Order By: Relevance
“…However, we found a lower nonunion rate (6%) if we compare our series with previous reports that show nonunion rates of more than 10% [1,6,12]. Nonunions are frequently related to the accuracy of the osteotomies performed at the hostallograft junctions.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, we found a lower nonunion rate (6%) if we compare our series with previous reports that show nonunion rates of more than 10% [1,6,12]. Nonunions are frequently related to the accuracy of the osteotomies performed at the hostallograft junctions.…”
Section: Discussionsupporting
confidence: 60%
“…The complications reported in this series did not differ from the expected in this kind of surgery [1,6,12]. However, we found a lower nonunion rate (6%) if we compare our series with previous reports that show nonunion rates of more than 10% [1,6,12].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Massive bone allograft and vascularized fibula graft, either alone or combined, are common biologic sources for reconstruction of intercalary defects after tumor resection, either as a primary or a salvage procedure [7]. When used alone, massive bone allografts are associated with complications such as nonunion at the host-allograft junction, allograft fracture, and infection [3,5,17,32]; by contrast, vascularized fibula grafts used alone or supplemental are associated with longer surgical times, risk of donor site morbidity, lengthy times to hypertrophy, and a high frequency of stress fracture [19]. Some studies have suggested that the shortcomings of each technique can be mitigated by using intercalary allografts in conjunction with a vascularized fibula autograft in primary and salvage situations, where immediate mechanical support is provided by the massive bone allograft allowing biologic activity of the vascularized fibula graft to result in hypertrophy and incorporation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…1 Allograft has its own shortcomings including infection and lower rates of union. 2 BMP is expensive and has limited Food and Drug Administration (FDA) approval. 3 An ideal surgery or bone substitute, that would cause 100% union rate in critical bone defects, is yet to be found.…”
Section: Introductionmentioning
confidence: 99%